El enigma del coronavirus – Reinfecciones por COVID-19, COVID prolongado – Vacunas bivalentes - La gestante – Derechos humanos y Ética - Romero, José Pacheco (2022)
At the end of the second year of the COVID-19 pandemic, it seems that the enigmaticcoronavirus is giving us some respite. However, the number of people infected hasstarted to rise in the northern hemisphere, where a strong winter with snowfall isapproaching. But this new increase is also observed in the southern hemisphere,as in Peru, when we are in spring. SARS-CoV-2 continues to differentiate into amultitude of variants and subvariants, some of which are more easily able to evadehuman immunity and that achieved with mRNA vaccines, and also may not respondto monoclonal antibody treatments. Current clinical information is oriented to theexpectation that existing vaccines could at least reduce hospitalizations, intensivecare admission and deaths. Learning about the clinical effects of SARS-CoV-2infection, the occurrence of reinfection, and long-term physical and mental harmcontinues, with prevention of infection, reinfection, and prolonged COVID beingsought.